No change in sight? Mirna Funk’s writing between Germany and Israel, memory, experience of violence, and emerging antisemitism - Preitschopf, Alexandra (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2026)
The article examines the novels Winternähe (2015) and Zwischen Du und Ich (2021) by the German-Jewish author Mirna Funk, exploring how the author portrays society and engages with various forms of structural violence, internal wounds, and traumas in a literary manner. While Winternähe primarily focuses on external events, openly addressing contemporary antisemitism and aiming to provide insight into the complex reality of Israeli life, Zwischen Du und Ich delves more deeply into internal processes, particularly focusing on the abuse of women. Both novels share the theme that the prospect of societal change is greatly diminished in the face of the numerous manifestations of violence depicted.